2015
DOI: 10.1128/jcm.01094-15
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study of Airway Mycobiome in Adult Cystic Fibrosis Patients: Differences in Community Structure between Fungi and Bacteria Reveal Predominance of Transient Fungal Elements

Abstract: The respiratory mycobiome is an important but understudied component of the human microbiota. Like bacteria, fungi can cause severe lung diseases, but their infection rates are much lower. This study compared the bacterial and fungal communities of sputum samples from a large cohort of 56 adult patients with cystic fibrosis (CF) during nonexacerbation periods and under continuous antibiotic treatment. Molecular fingerprinting based on single-strand conformation polymorphism (SSCP) analysis revealed fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 43 publications
5
62
1
Order By: Relevance
“…A recent analysis of fungal communities in cystic fibrosis sputum observed greater fluctuations in fungal richness, which contrasted with that for bacterial richness (77). Though chronic treatments with antibiotics during this period might have influenced the findings, the investigators nonetheless concluded that fungal elements detected in CF sputum are predominantly transient and likely related to inhaled sources.…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 89%
“…A recent analysis of fungal communities in cystic fibrosis sputum observed greater fluctuations in fungal richness, which contrasted with that for bacterial richness (77). Though chronic treatments with antibiotics during this period might have influenced the findings, the investigators nonetheless concluded that fungal elements detected in CF sputum are predominantly transient and likely related to inhaled sources.…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 89%
“…However, the association was mainly derived from two patients with preceding antibiotic therapy and antifungal therapy and the contribution of fungal or bacterial microbiota to lung function could not be distinguished. Despite variable fungal composition in LRT, Candida overall dominated mycobiota in most of the studies including CF patients, lung transplant patients, HIV infected patients and ICU patients (Bousbia et al, 2012; Charlson et al, 2012; Bittinger et al, 2014; Willger et al, 2014; Cui et al, 2015; Kramer et al, 2015a; Krause et al, 2016). In remaining studies with dominating fungi other than Candida methodologies were too weak to draw profound conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Observation periods varied between days (ICU patients; Krause et al, 2016), weeks (CF patients; Willger et al, 2014), 3 months to 1 year (CF patients; Delhaes et al, 2012), and months up to 2 years (CF patients; Kramer et al, 2015a). Conclusions are difficult to draw based on low numbers of individuals investigated, different patient groups and differences in time frames elapsing between sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations